2014
DOI: 10.1186/1687-9856-2014-8
|View full text |Cite
|
Sign up to set email alerts
|

Iodide transport: implications for health and disease

Abstract: Disorders of the thyroid gland are among the most common conditions diagnosed and managed by pediatric endocrinologists. Thyroid hormone synthesis depends on normal iodide transport and knowledge of its regulation is fundamental to understand the etiology and management of congenital and acquired thyroid conditions such as hypothyroidism and hyperthyroidism. The ability of the thyroid to concentrate iodine is also widely used as a tool for the diagnosis of thyroid diseases and in the management and follow up o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 137 publications
(142 reference statements)
2
57
0
6
Order By: Relevance
“…Seventy to 80% of the iodine content is located in the thyroid gland. [6] Organic binding of iodine in the thyroid is decreased when plasma iodide levels are elevated (acute Wolff–Chaikoff effect). Adaptation to this acute effect occurred in approximately 2 days, in the presence of constant high levels of iodide concentrations in plasma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventy to 80% of the iodine content is located in the thyroid gland. [6] Organic binding of iodine in the thyroid is decreased when plasma iodide levels are elevated (acute Wolff–Chaikoff effect). Adaptation to this acute effect occurred in approximately 2 days, in the presence of constant high levels of iodide concentrations in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Thyroid clearance varies depending on iodine intake, ranging from 10% of absorbed iodide in healthy individuals to more than 80% in patients with chronic iodine deficiency. [6] Guitierrez-Repiso et al [8] observed that in an adult population with adequate and stable nutrition, iodine excretion in a random urine sample represented 70% to 80% of daily iodine intake. Therefore, median urinary iodine concentrations (UIC) are widely used as a biomarker of population iodine intake, with levels >300 μg/L considered excessive in children and adults, and levels >500 μg/L considered excessive in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Регуляторное влияние половых гормонов на синтез НйС менее изучено. Имеются данные о способности эстрадиола подавлять экспрессию НйС [17]. В то же время в других исследованиях показано, что с наступлением половой зрелости в щитовидной железе самок происходит активация синтеза НйС [18].…”
Section: транскрипционная и посттранскрипционная регуляция синтеза нйсunclassified
“…Congenital hypothyroidism (CH) is the most common pediatric endocrine disorder [1,2]. CH is sporadic and occurs in 1:1500 to 1:4000 newborns, making it one of the most common causes of preventable mental retardation [3][4][5].…”
Section: Introductionmentioning
confidence: 99%